Vertebral strength prediction from Bi-Planar dual energy x-ray absorptiometry under anterior compressive force using a finite element model: An in vitro study. (November 2018) - Choisne, Julie; Valiadis, Jean-Marc; Travert, Christophe; Kolta, Sami; Roux, Christian; Skalli, Wafa
Abstract: Finite element models (FEM) derived from qCT-scans were developed as a clinical tool to evaluate vertebral strength. However, the high dose, time and cost of qCT-scanner are limitations for routine osteoporotic diagnosis. A new approach considers using bi-planar dual energy (BP2E) X-rays absorptiometry to build vertebral FEM using synchronized sagittal and frontal plane radiographs. The purpose of this study was to compare the performance of the areal bone mineral density (aBMD) measured from DXA, qCT-based FEM and BP2E-based FEM in predicting experimental vertebral strength. Twenty eight vertebrae from eleven lumbar spine segments were imaged with qCT, DXA and BP2E X-rays before destructively tested in anterior compression. FEM were built based on qCT and BP2E images for each vertebra. Subject-specific FEM were built based on 1) the BP2E images using 3D reconstruction and volumetric BMD distribution estimation and 2) the qCT scans using slice by slice segmentation and voxel based calibration. Linear regression analysis was performed to find the best predictor for experimental vertebral strength (Fexpe ); aBMD, modeled vertebral strength and vertebral stiffness. Areal BMD was moderately correlated with Fexpe (R 2 = 0.74). FEM calculations of vertebral strength were highly to strongly correlated with Fexpe (R 2 = 0.84, p < 0.001 for BP2E model and R 2 = 0.95, p < 0.001 for qCT model). The results of this study suggest that aBMD accounted for only 74% of Fexpe variability while FE models accounted for at least 84%. For anterior compressive loading on isolated vertebral bodies, simplistic loading condition aimed to replicate anterior wedge fractures, both FEM were good predictors of Fexpe . Therefore FEM based on BP2E X-rays absorptiometry could be a good alternative to replace qCT-based models in the prediction of vertebral strength. However future work should investigate the performance of the BP2E-based model in vivo in discriminating patients with and without vertebral fracture in a prospective study. Graphical abstract: Highlights: Finite Element models are better predictor of vertebral strength than DXA. Finite Element models accounted for at least 84% of the strength variability. BP2E X-ray Absorptiometry is a promising technique for vertebral strength prediction.